Acoustophoretic Motion of Erythrocyte‐mimicking Hemoglobin Micromotors. Issue 12 (24th September 2020) - Gao, Changyong; Lin, Zhihua; Zhou, Chang; Wang, Daolin; He, Qiang
Summary of main observation and conclusion: Biocompatible micromotors have received increasing attention, due to their powerful motion, diverse functionalities and autonomous navigation in the field of biomedical applications. Herein, we report an acoustically‐propelled, magnetic‐guided, erythrocyte‐mimicking hemoglobin micromotor with oxygen‐carrying capability. These hemoglobin micromotors were fabricated by encapsulating magnetic nanoparticles in hybrid hemoglobin/calcium carbonate microparticles, followed by covalently layer‐by‐layer assembly of hemoglobin multilayers. The asymmetric distribution of magnetic nanoparticles enables these micromotors to move rapidly under the propulsion of an acoustic field. The velocity of acoustophoretic motion of hemoglobin micromotors increases with the increase of input voltage of acoustic field, up to 58.2 μm·s –1 at 10 V. The hemoglobin micromotors are directionally navigated by applying an external magnetic field, and also could pass through microchannels toward the targeted region. Moreover, such hemoglobin micromotors show effective oxygen loading and releasing capability, holding considerable promise as a new platform for oxygen delivery applications. Abstract : Acoustically‐propelled erythrocyte‐mimicking hemoglobin micromotor with the biocompatibility and controlled motion is presented. Such micromotor could overcome the necessity of chemical fuels and provide a new approach for rapidly active oxygen delivery in a bio‐friendly manner.